Near room temperature plasma enhanced atomic layer deposition of ruthenium using the RuO4-precursor and H2-plasma. Issue 19 (21st May 2015) - Minjauw, Matthias M.; Dendooven, Jolien; Capon, Boris; Schaekers, Marc; Detavernier, Christophe
<x xml:space="preserve">Abstract</x> A plasma enhanced ALD process for Ru using RuO4 and H2-plasma is reported at sample temperatures ranging from 50 °C to 100 °C.